Germany : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix analyzes the link between Germany's economic performance and institutions, taking a long-term perspective and focusing on the labor market. The thesis of the paper is that Germany's institutional arrangements worked exceptionally well during the Wirtschaftswunder era of rapid catch-up growth, resulting in an economic performance that was envied by much of the world. The paper also examines fiscal consolidation and tax reform proposals, and describes the wage structure in Germany.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet